Nobel Prizes: Contributions to Cardiology - Mesquita,Evandro Tinoco (2015)
The Nobel Prize was created by Alfred Nobel. The first prize was awarded in 1901 and Emil Adolf von Behring was the first laureate in medicine due to his research in diphtheria serum. Regarding cardiology, Nobel Prize’s history permits a global comprehension of progress in pathophysiology, diagnosis and therapeutics of various cardiac diseases in last 120 years. The objective of this study was to review the major scientific discoveries contemplated by Nobel Prizes that contributed to cardiology. In addition, we also hypothesized why Carlos Chagas, one of our most important scientists, did not win the prize in two occasions. We carried out a non-systematic review of Nobel Prize winners, selecting the main studies relevant to heart diseaseamong the laureates. In the period between 1901 and 2013, 204 researches and 104 prizes were awarded in Nobel Prize, of which 16 (15%) studies were important for cardiovascular area. There were 33 (16%) laureates, and two (6%) were women. Fourteen (42%) were American, 15 (45%) Europeans and four (13%) were from other countries. There was only one winner born in Brazil, Peter Medawar, whose career was all in England. Reviewing the history of the Nobel Prize in physiology or medicine area made possible to identify which researchers and studies had contributed to advances in the diagnosis, prevention and treatment of cardiovascular diseases. Most winners were North Americans and Europeans, and male.